University Students' Motivation in Learning Arabic and English as Foreign Languages in Aceh - Yunisrina Qismullah Yusuf; Yuyun Nailufar; Raja Nor Safinas Raja Harun; Bustami Usman (Langkawi: Journal of The Association for Arabic and English, 2020)
This study explored the motivational types of English and Arabic language major students at one of the state Islamic universities in Banda Aceh, Indonesia. A questionnaire was given to 30 English and 30 Arabic major students to measure the level and type of students' learning motivation. A five-point Likert scale was used in the questionnaire, and the data were analyzed quantitatively using SPSS software. The results revealed that the English major students had a high integrative motivation in choosing English as their major compared to instrumental motivation (M=3.15˂M=4.19). Similarly, the Arabic major students dominantly had integrative motivation in learning Arabic compared to instrumental motivation (M=3.09˂M=4.29). The results further showed that integrative motivation could bring positive learning outcomes to the students because their goal of learning was to be accepted, and or be part of the language community they were learning. To conclude, English major students were enthused to study English because they wanted to be knowledgeable in English and used it to interact with other speakers of this language. In the same way, Arabic major students were also driven to learn Arabic for the sake of being knowledgeable in Arabic, to use it to interact with other people who use this language and to increase their appreciation towards the Arabic arts and literature. Finally, the findings of this study can increase awareness among students, teachers, researchers, and policymakers who work on enhancing motivation to increase students' interest in learning foreign languages at Indonesian universities.